Policy Analysis of Agricultural Modernization With “Berjaya” Farmer Card In Lampung Province, 2020 - Andrialius Feraera; Syuryansyah Syuryansyah (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
Facing the Agricultural Revolution 4.0 The Lampung Provincial Government is trying to make policy innovations on modernization of agriculture through the berjaya farmer card policy. however, in its implementation this policy faces several obstacles so that it is slow in its implementation. On this basis, this study aims to see how the facts of policies, the value of policies and actions taken by the government are for the success of the Berjaya Farmers Card policy. The method used in this research is descriptive qualitative. The technique of collecting data in this research is by making observations, interviews and documentation. The results show first, the fact that the 2020 farmer card triumphant card has entered the socialization and implementation stages even though the progress tends to be slow. Farmers who have joined this policy are only 0.8% of the total number of farmers in Lampung. The slow process of implementing this policy is also influenced by several factors, namely human resources, geographical factors, bureaucratic structure and conditions. Second, the value of this policy is still far from its planned goals. Third, the government needs to take actions including providing massive counseling and assistance to young (farmers millennial), increasing the quantity and quality of policy implementers, and widening cooperation with other private parties.